Analysis of the Phenomenon of Criminal Acts Involving Minors and its Impact on Law Enforcement at the Kayong Utara Police, West Kalimantan - Susanto, Robertus Hadi; Vic, Binsar Jon (Devotion : Journal of Research and Community Service, 2025)
The phenomenon of criminal acts involving minors in Indonesia, especially in the Kayong Utara Police area, West Kalimantan, has become a serious concern in the context of law enforcement. Cases involving children as perpetrators or victims of criminal acts pose a challenge to the justice system, given the differences in the legal treatment of children and adults. This study aims to analyze the forms of criminal acts involving minors in the area, as well as their impact on law enforcement, both in terms of the implementation of child protection regulations and applicable legal procedures. Through this study, it is expected to find a solution to increase the effectiveness of law enforcement and provide maximum protection for children involved in criminal acts.